Fungal, parasitological, and bacterial coinfection in a severely ill COVID- 19 patient in Peru - Moya-Salazar, Jeel (2022)
COVID- 19 patients are prone to coinfections during their hospitalization. These coinfections are challenging as they involve longer hospital stays, high costs, and higher risk of mortality. Here, we present a case of a patient with multi- infection by resistant parasites, fungi, and bacteria during his hospitalization in a hospital in Lima, Peru